2022
DOI: 10.3390/plants11233293
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Biology of Coconut (Cocos nucifera L.)

Abstract: Coconut (Cocos nucifera L.) is an important perennial crop adapted to a wide range of habitats. Although global coconut demand has increased sharply over the past few years, its production has been decreasing due to palm senility, as well as abiotic and biotic stresses. In fact, replanting efforts are impeded due to the lack of good quality seedlings. In vitro technologies have a great potential; however, their applications may take time to reach a commercial level. Therefore, traditional seed propagation is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…The results indicated that pre-treatment could further enhance the success of tissue culture. It was speculated that the storage pre-treatment might activate the internal germination mechanism of the coconuts, imparting greater vitality to the explants [29]. Storing the coconut fruits for 15 days during shipment would not pose an issue and could even boost the callusing rate, which links back to the previous concern regarding long-distance shipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that pre-treatment could further enhance the success of tissue culture. It was speculated that the storage pre-treatment might activate the internal germination mechanism of the coconuts, imparting greater vitality to the explants [29]. Storing the coconut fruits for 15 days during shipment would not pose an issue and could even boost the callusing rate, which links back to the previous concern regarding long-distance shipment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism still remains unknown, further research being required with regard to this scientific issue. A storage process can also be considered as a pretreatment for embryos, facilitating germination processes during the storage period [29]. This may be the reason why stored coconut demonstrated a better performance regarding somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Low temperature poses a critical challenge, impeding the natural growth of coconuts and serving as one of the detrimental abiotic stresses that affect their topographical distribution ( Yang et al., 2018 ). The optimal temperature for coconut growth is 27-32°C, with yearly average temperature of 29°C ( Beveridge et al., 2022 ). Low temperature not only inflicts severe damage on low-temperature sensitive coconut varieties at seedlings stage, but also leads to fruit drop, uneven accumulation of coconut flesh and decreased quality of coconut water in mature plants.…”
Section: Introductionmentioning
confidence: 99%
“…Palm trees play a dual role as both a vital source of food, supporting local economies and providing essential nutrients, and as ornamental plants, enhancing landscapes, cultures, and recreational spaces. Balancing the economic benefits of palm cultivation with sustainable practices and conservation efforts is crucial to ensure the long-term viability of these significant plant species [20] . Many palm products, such as coconuts and dates, are rich in essential nutrients, including vitamins, minerals, and healthy fats.…”
Section: Introductionmentioning
confidence: 99%